2020
DOI: 10.1111/anu.13108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium supplementation on the antioxidation response in the rotifer ( Brachionus plicatilis )

Abstract: In the present study, the effects of selenium (Se) enrichment on the rotifer, Brachionus plicatilis, were investigated. Based on the results of six Se treatments obtained from triplicate experiments, we found that the efficiency of bioaccumulation by Se from non‐acid‐soluble sources was 62‐fold greater than that from acid‐soluble sources (Se‐Chlorella 15.6 ± 1.81% vs. selenite 0.25 ± 0.03%). However, supplementation of both acid‐soluble Se at low concentrations (≤40 µg per thousand rotifers) and Se‐Chlorella e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Rotifers select food in the range of 4-10 µm, and using I. galbana and N. oculata enriched with minerals is more appropriate than Se-enriched C. vulgaris with a size of more than 15 µm (Sun et al, 2020). In this study, Sun et al (2020) showed that rotifer fed on Chlorella pyrenoidesa with 4 µm size gave better results than using C. vulgaris. Thus, one of the reasons for the low growth of the rotifer fed the 5 and 10 mg L −1 treatments, especially the latter, might be that the microalgae size was lower than the optimal to feed rotifers.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Rotifers select food in the range of 4-10 µm, and using I. galbana and N. oculata enriched with minerals is more appropriate than Se-enriched C. vulgaris with a size of more than 15 µm (Sun et al, 2020). In this study, Sun et al (2020) showed that rotifer fed on Chlorella pyrenoidesa with 4 µm size gave better results than using C. vulgaris. Thus, one of the reasons for the low growth of the rotifer fed the 5 and 10 mg L −1 treatments, especially the latter, might be that the microalgae size was lower than the optimal to feed rotifers.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, 2 mg L −1 was the best group in terms of growth (population density, egg number, egg ratio, SGR, N max and DT), contained the second‐highest level of Zn (69.26 ± 0.60 µg g −1 DW) and the amount of Se was 103.45 ± 4.99 µg g −1 DW. According to published results (Penglase et al, 2011; Sun et al, 2020), the amount of Se that is non‐toxic in rotifers is 22–113 µg g −1 DW, with the amount obtained using the 2 mg L −1 enrichment treatment being in this range. The highest specific growth rate (0.61 ± 0.03 day −1 ) was observed in the group fed with 2 mg L −1 of minerals, which is equal to the population growth rate of the rotifer fed with 3.3 μg g −1 DW Se‐enriched C .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations